Consciousness Not Without Danger: Theorising Violence Faced by Dalit Converts - Afsara Ayub (Caste)
The present article views Dalit conversion as a gradual process or bottom-up reassessment strategy for a democratic environment assumed to provide a space to challenge the social structure of the Hindu caste system. To theorise this, the article deploys Victor Turner’s concept of liminality and studies religious conversion as a transition, liminal process, or threshold that promises to bring change and alternation in the existing rigid structure. It aims to provide a nuanced understanding of how religious conversion functions as a space of both rupture and renewal in Dalit identity formation. The epigram of this article spells out the objectives to show when, why, and how they follow the path of conversion. It argues that due to their peculiar position in the Hindu caste hierarchy and exclusion from the Varna category, Dalits are open to change their religion from Hinduism to another religion. The willingness to change their Hindu religion either in the form of protest and assertion, or compulsion to escape from the practice of untouchability, explains the capacity of Dalits to break the caste structure and possibly become an entirely new self. Furthermore, the article argues that this process of becoming a new self is surrounded by danger; Dalits, as transgressors, who challenge the social stratification of the Hindu caste system by converting to other religions, are often drawn to violence. The prevalence of the concept of conversion as a consciously chosen path by Dalits strikes controversy among caste Hindus, and the flexibility with which Dalits approach religion becomes one of the main causes of violence. Finally, it argues that when Dalit consciousness manifests itself through conversion, it invites danger, threat, or violence, and this threat and violence may not necessarily appear in physical and overt form but in covert forms such as violations of certain constitutional rights.